Coherent X-ray scattering reveals nature of dynamical transitions in nanoparticle–polymer suspensions. (22nd November 2016) - Chandran, Sivasurender; Begam, N.; Sprung, M.; Basu, J.K.
Abstract: We report the microrheological behavior and dynamics of the suspensions of polystyrene-grafted gold nanoparticles (PGNPs) mixed with linear polystyrene (PS) as a function of the PS concentration and size asymmetry parameter, ξ (= M g / M m, with M g and M m being the grafted and free chain molecular weights, respectively) = 2.76 and 0.14. Diffusive wave spectroscopy (DWS) is used for measuring the frequency dependent micro-rheology parameter, the loss modulus G ″ ( ω )(∼ ω α ). For suspensions with ξ = 0.14 a transition of α, from ∼1 to ∼1.6, is observed at a critical fraction of added polymers. On the other hand, α is always ∼1 for the suspensions with ξ = 2.76. Corresponding x-ray photon correlation spectroscopy (XPCS) data on the same samples reveals a sharp transition in the nature of dynamics of PGNPs, from exponential to logarithmic, in suspensions with ξ = 0.14, while for suspensions with ξ = 2.76 this dynamical transition is not observed. Interestingly, the dynamical transition in ξ = 0.14 based samples occurs at the same fraction of added polymers, where the transition of α from ∼1 to ∼1.6 was observed, thus providing a clear correlation between microscopic dynamics and micro-rheology. The conformational transitions of the grafted polymers is found to be the reason behind the observed differences in the dynamic behavior of the two systems. The important role of advanced x-ray scattering techniques in unravelling subtle aspects of nanoscale complex polymer and soft colloidal dynamics is thus revealed. Graphical abstract: Highlights: Micro-rheological transitions were correlated with the underlying microscopic dynamics through coherent X-ray scattering. Osmotic shrinkage/swelling of the grafted polymers is observed in the presence of linear polymers with different sizes. A morphological model is proposed to explain the observations.